2016
DOI: 10.3847/0004-637x/830/2/137
|View full text |Cite
|
Sign up to set email alerts
|

After the Interaction: An Efficiently Star-Forming Molecular Disk in NGC 5195

Abstract: We present new molecular gas maps of NGC 5195 (alternatively known as M51b) from the Combined Array for Research in Millimeter Astronomy, including 12 CO(1-0), 13 CO(1-0), CN(1 0,2 -0 0,1 ), CS(2-1), and 3 mm continuum. We also detected HCN(1-0) and HCO + (1-0) using the Onsala Space Observatory. NGC 5195 has a 12 CO/ 13 CO ratio ( 12 13 =11.4 ± 0.5) consistent with normal star-forming galaxies. The CN(1-0) intensity is higher than is seen in an average star-forming galaxy, possibly enhanced in the diffuse … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 97 publications
(149 reference statements)
5
21
1
Order By: Relevance
“…even smaller values than those probed by our simulations 1 ), which suggests to adopt values of α CO comparable or even higher to that of disks. Our findings thus support the high values of α CO they used (∼ 4 -6, instead of choosing a ULIRG value of α CO = 0.8, see their figure 12), and thus their conclusion of star formation efficiencies lower in their post-starburst galaxies than in disks despites large amount of CO gas, for a reason yet to be determined (French et al 2018, but see also Alatalo et al 2016 for the opposite conclusion from different galaxy selection criteria).…”
Section: Discussionsupporting
confidence: 83%
“…even smaller values than those probed by our simulations 1 ), which suggests to adopt values of α CO comparable or even higher to that of disks. Our findings thus support the high values of α CO they used (∼ 4 -6, instead of choosing a ULIRG value of α CO = 0.8, see their figure 12), and thus their conclusion of star formation efficiencies lower in their post-starburst galaxies than in disks despites large amount of CO gas, for a reason yet to be determined (French et al 2018, but see also Alatalo et al 2016 for the opposite conclusion from different galaxy selection criteria).…”
Section: Discussionsupporting
confidence: 83%
“…Additionally, this galaxy shows enhanced 24µm emission ( Figure 2) and elevated dust temperature (Mentuch Cooper et al 2012) compared to M51. M51b is a barred lenticular galaxy in a post-starburst phase, in which the stellar population is dominated by old stars ( 10 Gyr) and massive star-formation is suppressed (Kohno et al 2002;Alatalo et al 2016). The lack of massive star formation in M51b is consistent with the faint [C ii] emission detected but it is inconsistent with the large TIR emission observed in this galaxy and the high SFR inferred from Hα and 24µm dust continuum emission.…”
Section: The Origin Of the [C Ii] Deficit In M51bmentioning
confidence: 83%
“…The red line denotes the result of a Gaussian fit and the grey area the expected velocity range of the integrated CO emission observed in M51b (Kohno et al 2002). at the center of the galaxy, [C ii] shows emission only from the South-West (S-W) side of the TIR peak. CO observations show a molecular disk in M51b that extends to the S-W and North-East (N-E) from its center (Kohno et al 2002;Alatalo et al 2016). The S-W and N-E components have CO velocities of ∼580 km s −1 and ∼680 km s −1 , respectively (Kohno et al 2002).…”
Section: The Origin Of the [C Ii] Deficit In M51bmentioning
confidence: 99%
“…Resolved measurements by Kohno et al (2002) using the Nobeyama Millimeter Array are brighter than the 15″ beam unresolved observations. Alatalo et al (2016a) reobserved this galaxy using the Combined Array for Research in Millimeter Astronomy and found a CO (1-0) line flux in between the two Kohno et al (2002) measurements. NGC 5195 has both HCN and CO luminosities consistent with its SFR from Lanz et al (2013), unlike our targets.…”
Section: Dense Gas In Other Post-starburst-like Galaxiesmentioning
confidence: 95%